A diagnosis of students' errors in answering the mathematics test in senior high school - Evana Gina Shantika; Edi Istiyono (Jurnal Penelitian dan Evaluasi Pendidikan, 2019)
This study aims to reveal: (1) the characteristics of diagnostic test items used in mathematics subject of the first grade of senior high school (SHS); (2) the degree of errors from several types of students’ errors in answering mathematics test; and (3) the dominant factor causing the students to make mistakes in answering mathematics test. This study used a quantitative approach involving the first graders of eight SHSs in Mataram as the population. The sample was collected by a proportionate random sampling technique, consisting of 350 students for preliminary field testing and 450 students for main field testing. The research instrument was a mathematics diagnostic test, questionnaire, and interview guidelines. The results show that: (1) the diagnostic test instrument meets the qualitative and quantitative content validity, proves empirically fit with Partial Credit Model (PCM), has reliability index of 0.92 (high category), and all items in the diagnostic test instrument are categorized in moderate difficulty; (2) misrepresentation becomes dominant errors if compared with misconceptions, the counting errors, and procedural errors. The errors dominant in the topic domain are Inequalities Linear System Two Variables if compared with Rational and Irrational Inequality One Variable, Equations and Inequalities of Absolute Value, and Linear Equations System Three Variables; and (3) most of the students do not understand how to solve the problem of inequality, determining factor quadratic equations, determining the members of the set completion, problems concerning graphs, and problems that require the capability of language interpretation into the mathematics model.